Mapping of Digital Financial Literacy Research: A Bibliometric Review - Kartini, Kartini; Pahlevi, Reza Widhar; Rachmi, Nur Habiba (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
This study aims to review digital financial literacy based on the previously-published articles. A literature study based on the Scopus database from 1984 to 2022 is conducted by employing the VOSviewer tool to analyze the collected data for the bibliometric analysis. The findings point toward the people’s behavior on investment decisions. The questionnaire is the most widely used data collection method, and the conversations are evenly shared in developing and developed countries. The key themes are still divided into financial inclusion and general digital finance issues. Discussion and future research are provided.